The Principal's Strategy in Instilling Islamic Values in A Multicultural School - Fatmaya Anisa Rahmania; Muh Hanif (IQRO: Journal of Islamic Education, 2025)
This study aims to analyze the principal’s leadership strategies in instilling moderate Islamic values within a multicultural school environment. The research was conducted at SMK Negeri 1 Purwokerto, utilizing a qualitative approach with a case study and phenomenological methods. Data were collected through in-depth interviews with the principal, Islamic education teachers, and students, as well as through observations and document analysis. The findings reveal that the principal's strategies employ a holistic approach that integrates spiritual, social, and academic values, as well as role modeling by teachers and students, and the contextual adaptation of religious programs in an inclusive manner. The values of tasamuh (tolerance) and ‘adl (justice) serve as the foundation for fostering social harmony. These findings highlight the effectiveness of moderate Islamic approaches in strengthening students’ religious character while creating a tolerant and inclusive educational ecosystem in public schools.